Changes in the Gut Microbiome Contribute to the Development of Behcet’s Disease via Adjuvant Effects - Wang, Qingfeng; Yi, Shenglan; Su, Guannan; Du, Ziyu; Pan, Su; Huang, Xinyue; Cao, Qingfeng; Yuan, Gangxiang; Kijlstra, Aize; Yang, Peizeng (Frontiers in Cell and Developmental Biology, 2021)
Behcet’s disease (BD) is associated with considerable gut microbiome changes. However, it still remains unknown how the composition of the gut microbiome exactly affects the development of this disease. In this study, transplantation of stool samples from patients with active ocular BD to mice via oral gavage was performed. This resulted in decreases of three short chain fatty acids (SCFAs) including butyric acid, propionic acid and valeric acid in the feces of the BD-recipient group. Intestinal barrier integrity of mice receiving BD feces was damaged as shown by a decreased expression of tight junction proteins and was associated with the release of Lipopolysaccharides (LPS) in the circulation. The mice also showed a higher frequency of splenic neutrophils as well as an enrichment of genes associated with innate immune responses in the neutrophils and CD4 + T cells as identified by single cell RNA sequencing. Analysis of neutrophils and T cells functions in these mice showed an enhanced mesenteric lymph node and splenic Th1 and Th17 cell differentiation in association with activation of neutrophils. Transplantation of BD feces to mice and subsequent induction of experimental uveitis (EAU) or encephalomyelitis (EAE) led to an exacerbation of disease in both models, suggesting a microbial adjuvant effect. These findings suggest that the gut microbiome may regulate an autoimmune response via adjuvant effects including increased gut permeability and enhancement of innate immunity.